Single Cell RNA Sequencing of Rare Immune Cell Populations - Nguyen, Akira; Khoo, Weng Hua; Moran, Imogen; Croucher, Peter I.; Phan, Tri Giang (Frontiers in Immunology, 2018)
Single-cell RNA sequencing (scRNA-Seq) is transforming our ability to characterize cells, particularly rare cells that are often overlooked in bulk population analytical approaches. This has lead to the discovery of new cell types and cellular states that echo the underlying heterogeneity and plasticity in the immune system. Technologies for the capture, sequencing, and bioinformatic analysis of single cells are rapidly improving, and scRNA-Seq is now becoming much more accessible to non-specialized laboratories. Here, we describe our experiences in adopting scRNA-Seq to the study of rare immune cells in their microanatomical niches.